THE EFFECT OF CARTOON PICTURES IN COLORED ENVELOPES ON THE GRAMMAR MASTERY OF THE 7TH GRADERS AT SMPN 1 GLAGAH IN THE ACADEMIC YEAR 2023-2024 - Ni Wayan Fiana Anjani Putri; Yuli Sugianto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The title of this research is “The Effect of Cartoon Pictures in Colored Envelopes on the Grammar Mastery of the 7th Graders at SMPN 1 Glagah in the Academic Year 2023-2024”. It is written to be submitted to the English Educational Department of PGRI University of Banyuwangi. The respondents of the research are seventh grade students at SMPN 1 Glagah academic year 2023/2024. In this research, the researcher took one class as the sample. The subject research is class VIIC which consists of 31 students. The objective of this research is To determine whether or not there is any effect of Cartoon Pictures in Colored Envelopes on the Grammar Mastery of the 7th year graders at SMPN 1 GLAGAH. The researcher conducted this research for three times of meeting, first day for pre-test, second day for treatment and last day for post-test. The method used in this research is quantitative with a one group pretest-posttest research design. The researcher used test as the instrument. After the data was obtained, the researcher calculated the data using the Wilcoxon test. Based on the calculation results, the pretest average was 34.86 and the posttest average was 77.91. To determine the truth of the hypothesis, the result of Wilcoxon test is 0.000, which is a lower value when viewed from the significance level of 0.05 used (0.000 < 0.05). It can be concluded that the hypothesis "Use cartoon pictures in colored envelopes as a learning media is effective on students' grammar mastery of the 7th graders at SMPN 1 Glagah in the academic year 2023-2024 is accepted”